New-onset acute thrombocytopenia in hospitalized patients: pathophysiology and diagnostic approach - Naveed Ali; Herbert E. Auerbach (Greater Baltimore Medical Center, 2017)
Thrombocytopenia is a hematological finding commonly encountered in daily clinical practice from asymptomatic clinic patients to critically ill intensive care unit patients. A broad spectrum of etiologies and variation in clinical presentation often present a diagnostic challenge. Furthermore, concomitant presence of thrombosis and thrombocytopenia, as in cases of thrombotic thrombocytopenia, complicates the management. In hospitalized patients, new-onset thrombocytopenia is an important reason for hematology consultation. Therefore, it is of utmost importance that the etiology is diagnosed accurately. In addition, a basic understanding of the pathophysiology and the differential diagnosis avoids delay in the diagnosis and leads to rapid initiation of treatment. This review will address causes of thrombocytopenia that arises in hospitalized patients with an emphasis on the pathophysiological basis of each disorder.